2000
DOI: 10.1128/aem.66.10.4468-4474.2000
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Segregation of the Neurotoxin-Producing Cyanobacterium Anabaena circinalis

Abstract: Blooms of the cyanobacterium Anabaena circinalis are a major worldwide problem due to their production of a range of toxins, in particular the neurotoxins anatoxin-a and paralytic shellfish poisons (PSPs). Although there is a worldwide distribution of A. circinalis, there is a geographical segregation of neurotoxin production. American and European isolates of A. circinalis produce only anatoxin-a, while Australian isolates exclusively produce PSPs. The reason for this geographical segregation of neurotoxin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 35 publications
1
73
2
Order By: Relevance
“…Within the Dolichospermum genus, saxitoxin production has been only reported in D. circinalis (Anabaena circinalis) blooms in Australian freshwater systems, such as dams, weirs on rivers, and reservoirs (Beltran and Neilan, 2000). The gene cluster responsible for saxitoxin biosynthesis (genes sxtA-E and sxtG-X spanning 28 kbp) has been described for D. circinalis (Mihali et al, 2009) (Fig.…”
Section: Saxitoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the Dolichospermum genus, saxitoxin production has been only reported in D. circinalis (Anabaena circinalis) blooms in Australian freshwater systems, such as dams, weirs on rivers, and reservoirs (Beltran and Neilan, 2000). The gene cluster responsible for saxitoxin biosynthesis (genes sxtA-E and sxtG-X spanning 28 kbp) has been described for D. circinalis (Mihali et al, 2009) (Fig.…”
Section: Saxitoxinmentioning
confidence: 99%
“…It has been estimated that about half of the cyanobacterial strains in culture collections have been misidentified (Komá rek and Anagnostidis, 1989). Several studies have cautioned against the over-emphasis on morphological characters for identification and taxonomic classification (Beltran and Neilan, 2000;Rajaniemi et al, 2005a,b;Zapomělová et al, 2007Zapomělová et al, , 2010b.…”
Section: Phylogenetic Divergence Within the Genus Dolichospermummentioning
confidence: 99%
“…PSPs are potent blockers of voltage-dependent sodium-channels and therefore restrict transmission between neurons. In contrast to the only PSPproducing Australian strains, European and American strains of Anabaena circinalis appear to exclusively synthesize anatoxins (Beltran and Neilan, 2000). In general, the genus Anabaena can produce MCs, PSPs and anatoxin-a with toxin contents of 2 mg/g dry weight (DW) for MCs (Rapala and Sivonen, 1998), 4.4 mg/g DW for PSPs (Velzeboer et al, 2000) and a remarkable 28 mg/g DW for anatoxin-a (Rapala and Sivonen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Beltran & Neilan (2000) found a close relationship between the A. flos-aquae AWQC112D strain and several A. circinalis strains, and reported that no other clone of A. flos-aquae except for this one from Australia has appeared in such a position. Our finding about strains DC-1, DC-2, and EH-1 adds new information on the distribution of A. flos-aquae strains and supports that there exist probably two branches of this morphotype (Beltran & Neilan, 2000). According to the phylogenetic analysis of 16S rRNA genes, strains EH-2, EH-3, and EH-4 were very close to the group which included some A. circinalis and A. crassa strains.…”
Section: Discussionmentioning
confidence: 99%